The Challenge of Human Resource Management Toward Industrial Revolution 4.0 for Manufacturing Sector in Indonesia: Literature Study - Nadya Jasmine Rahmadani (Community Engagement and Emergence Journal (CEEJ), 2026)
The Industrial Revolution 4.0 has significantly transformed the business landscape through the integration of digital technologies, automation, artificial intelligence and big data, posing substantial challenges for human resource management (HRM), particularly in the manufacturing sector in Indonesia. This article aims to analyze the key challenges faced by HRM in adapting to the demands of Industry 4.0 and to identify strategic responses required to enhance organizational competitiveness. Using a qualitative descriptive approach based on a review of relevant literature, policy documents, and industry reports, the study examines issues such as the digital skills gap, workforce reskilling and upskilling, changes in employment relationships, organizational culture transformation, and the readiness of HR systems to support digitalization. The findings indicate that many manufacturing sector organizations in Indonesia face limitations in human capital quality, unequal access to technology, and resistance to change, which hinder effective implementation of Industry 4.0 initiatives. Therefore, HRM is required to play a more strategic role by developing agile talent management, continuous learning systems, and adaptive leadership. This study concludes that the success of Indonesia’s private sector in the era of Industrial Revolution 4.0 largely depends on the ability of human resource management to proactively manage technological change while maintaining employee engagement and productivity.